Development in a bee line - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Strengthening Livelihoods. Exploring the Role of Beekeeping in Development N Bradbear, E Fisher & H Jackson, Bees for Development, UK, 2002. 122 pp. ISBN 1 898807 01 9 GBP 27.50 Euro 42.50